Tata Niaga, Nilai Ekonomi dan Kualitas Kulit Kayu Masohi di Kabupaten Fakfak Provinsi Papua Barat - Hegemur, Siti Hanafiah; pono, wahyudi sayuti; Nugroho, Bambang; Mahmud (Median : Jurnal Ilmu Ilmu Eksakta, 2024)
Massoi (Cryptocarya massoi (Oken) Kostem) is non-timber forest products of spices utillized for as food flavour, traditional medicine, and pharmacheutical material. This research is designed to describe the market chain, economic values, natural disturbance in local farming lands, natural regenarion, legal harvesting permit, and evaluate masohi bark quality to SNI 7941:2013, and determine an intervention for to increase the added values for local farmers. This research was undertaken in 13 villages at 6 subdistricts in Fakfak district West Papua. Interviews based on the questioner and field survey were conducted to collect the data. The results indicated that qualitatively local farming land for Masohi is 102,5 ha in total with for an average distance of 3.23 km form their homes. These farming land are scattered in both secondary and primary forest, cultivated with agroforestry system and planted insite ot in between Myristica trees. Regenerations are done using local nursery and natural sapling from the mother trees. Prices of the dried masohi bark have vary, at farmer IDR 50.000 – 60.000/kg, local collecter traders IDR 70.000/kg and legal harvesting permit holders for IDR 120.000/kg. An innovation for producing packaging masohi products with labels, standaritation and certification could provide significant impact on the added value for local farmers. The majoritas (53,85%) for legal harvesting permit is non-local communities. Local regulation is needed to gain the added values for masohi farmers. Masohi bark collected from Fakfak district could be utilized for raw material for Jamu and essential oil but properly drying is required to reduce the moisture content and elimate fungi contamination.